Relationship between Postpartum Diseases and Success of First Artificial Insemination in Dairy Cattle - Cikita, Diah Ayu; Subagio, Reza Taufiq; Septiyani, Septiyani; Setiawan, Vincentius Mubiarto; Kristanto, Dwi (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Ketosis, mastitis, metritis, and LDA are diseases that often occur during the first two weeks of lactation and cause significant economic loss. The relationships between ketosis, mastitis, metritis, LDA, and several combinations of diseases and the first artificial insemination were discussed. This study aimed to describe the effect of diseases diagnosed during the postpartum period on the success of artificial insemination. This study was conducted using an observational cross-sectional approach. A total of 341 data samples were obtained, which consisted of 103 cattle without disease, 107 cattle diagnosed with ketosis, 51 cattle diagnosed with metritis, 5 cattle diagnosed with LDA, 20 cattle diagnosed with a combination of ketosis and mastitis, 20 cattle diagnosed with a combination of ketosis and metritis, and 6 cattle diagnosed with a combination of mastitis and metritis. Data analysis was carried out using bivariate analysis and tested using the chi-square test. The P values for ketosis, mastitis, metritis, LDA, ketosis-mastitis, ketosis-metritis, and mastitis-metritis were 0.756, 0.099, 0.972, 0.261, 0.276, 0.276, and 0.450, respectively. This study suggested that a history of disease during the postpartum period did not significantly affect cattle first artificial insemination.